Is the treatment of ankle osteoarthritis changing over time in Italy? Analysis of temporal trends for fusion and arthroplasty in a population-based study from 2001 to 2022 on the National Hospital Discharge Record database - Adriano Cuccu; Elena Manuela Samaila; Enrico Ciminello; Umberto Alfieri Montrasio; Fabrizio Cortese; Stefania Ceccarelli; Tiziana Falcone; Marina Torre (Journal of Orthopaedics and Traumatology, 2025)
Abstract Background Treatment of ankle osteoarthritis by total ankle replacement (TAR) is increasing worldwide. The aim of the study was to present the overall temporal trends of TAR throughout 22 years (2001–2022) in Italy, analyzing the distributions of hospitals by volume of activity and patients by age and sex, drawing on the National Hospital Discharge Record database. Furthermore, as a secondary aim, we compared these trends with those of ankle fusions. Materials and methods International Classification of Diseases, 9th Revision, Clinical Modification (ICD9-CM) codes of interest were identified to browse the Italian National Hospital Discharge Record database. Surgical volumes, trends over time, classes of hospital activity volume, sex and age of patients, and population incidence rates were described. The statistical significance of time series trends was assessed by the Cox–Stuart test with randomness as a null hypothesis. Results 20,248 ankle procedures (total ankle replacements 8853 and ankle fusions 11,395) were extracted from 231,601,523 admissions registered nationally from 2001 to 2022. The yearly total number of TARs significantly increased almost tenfold from 96 to 996 (p < 0.05), while the number of fusions exhibited a stationary behavior (p > 0.05). The increased trend in TAR procedures was concentrated mostly in the North of Italy, with predominantly males between 55 and 64 years of age. The analysis of the number of procedures performed on inhabitants by region and that performed by all the hospitals in the region showed a different pattern across Italy. Conclusions The substantial increase in TARs may be owing to improved implant designs and innovative surgical technologies, which allow the treatment of more severe cases and deformities, previously untreated or treated by a fusion. This trend highlights the need to invest in implementing high quality registries by promoting surgeons’ participation in data collection. Level of evidence: population based study, level 1 evidence.